Pelaksanaan Sita Jaminan Terhadap Objek Sengketa Yang Berada Di Tangan Pihak Ketiga Dalam Penanganan Perkara Perdata - Teguh Syuhada (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
Civil procedure Code regulates an institution called the seizure of property  (conservatoir beslag) which is regulated in Article 261 RBG or 227 Paragraph (1) HIR. Article 261 The RBG explains as follows: If there are reasonable grounds, that a person is in debt, before the decision is made, or before the verdict that defeats it cannot be implemented, but in order to provide certainty and a sense of justice for the parties in the civil case the role of the institution is needed confiscation guarantee. The confiscation institution is considered able to keep the disputed goods from the defendant's actions so that it can guarantee the plaintiff's interests can be protected. In practice the seizure guarantee in the lawsuit is granted by the judge and declared valid and valuable will automatically become executorial seizure in order to support the decision. Parties with an interest in the rights of the object disputed in a civil suit shall, at the request of the person concerned, the Chairperson of the District Court give the order to confiscate the object of the dispute in order to safeguard. In practice, seizure guarantees do not always go well, especially for collateral seizure, where the object of the dispute is in the hands of a third party, so that the importance of reviewing the confiscation process is in the hands of third parties in the object of handling civil cases.